Short-term Forecasting of Covid-19 Cases in East Java of Indonesia using NARX-NN Model - Hermansah; Rosadi, Dedi; Novianti, Pepi (JINAV: Journal of Information and Visualization, 2023)
The goal of this study is to forecast short-term verified Covid-19 infections in East Java of Indonesia using the NARX-NN model. Here, the external variable used was the weather of East Java. The confirmed data for Covid-19 were obtained from the BNPB, and the weather data of East Java were obtained from the BMKG. Data from July 21st, 2020 to June 20th, 2021, were used for model formation (training data), and data from June 21st to 27th, 2021 were used for validation data. Based on the formatting model results, we can conduct a short-term forecast for three future periods (June 28th to 30th, 2021). This research evaluated the NARX-NN model using the forecasting accuracy of MAPE. The NARX-NN approach is more suitable than the NAR-NN method for predicting daily confirmed Covid-19 cases in East Java, based on the forecasting results of the NAR-NN and NARX-NN methods. The MAPE value was 0.03060 (0.03248 smaller than the MAPE value of the NAR-NN). At the conclusion of the study, the NARX-NN approach was utilized for daily forecasting of Covid-19 instances in East Java from June 28th to June 30th, 2021, namely 1039, 1072, and 1185.